FACTORS INFLUENCING PURCHASING BEHAVIOUR OF VETERINARY PHARMACEUTICALS IN SOUTH AFRICA - Simpson, Brett (My University, 2011)
Veterinary pharmaceutical companies in South Africa operate in a very competitive environment. Understanding the buying centre and consumer behaviour of a veterinary practice will enable these companies to effectively reach their target market. This research specifically investigated which members of a veterinary practice form the buying centre and what the level of involvement is in the purchasing decision process. The objective was to determine what the most important selection criteria are when purchasing veterinary pharmaceutical products and to identify any differences between three product categories of veterinary pharmaceuticals viz. Biologicals, Ethicals and Veterinary Over the Counter products. Moreover, the relative importance’s of different sources of information were investigated as well as any variances between the product groups. Gender, age, ownership status, number of vets per clinic and consultation fee were used to determine if the veterinary market could be segmented. The research was conducted across South Africa by means of a structured questionnaire. The total sample comprised 327 respondents, with the data collected then being analysed using descriptive and inferential statistics. The research exposed that there are certain differences between the product groups when considering both the selection criteria and information sources. The important purchasing decision criteria included inter alia experience with the product, efficacy and safety of the product, technical information on the product, price and service levels provided by the pharmaceutical company. The important information sources included sales representatives, scientific journals and veterinary colleagues. Suggestions for segmenting the veterinary market seemed limited based on the demographic variables investigated. A dashboard of attributes for each of the product groups are suggested as a basis upon which marketing strategies can be developed. The research highlighted the need to understand the buying centre of a veterinary practice and to understand the buying behaviour thereof. The successful veterinary pharmaceutical company is one that will be able to create successful synergies with these important attributes. This will ensure the best return on a limited set of marketing resources.
MBA - WBS
Keywords: Veterinary pharmaceuticals; Purchasing behaviour